Novel Ethanol- and 5-Hydroxymethyl Furfural-Stimulated β-Glucosidase Retrieved From a Brazilian Secondary Atlantic Forest Soil Metagenome - Alves, Luana de Fátima; Meleiro, Luana Parras; Silva, Roberto N.; Westmann, Cauã Antunes; Guazzaroni, María-Eugenia (Frontiers in Microbiology, 2018)
Beta-glucosidases are key enzymes involved in lignocellulosic biomass degradation for bioethanol production, which complete the final step during cellulose hydrolysis by converting cellobiose into glucose. Currently, industry requires enzymes with improved catalytic performance or tolerance to process-specific parameters. In this sense, metagenomics has become a powerful tool for accessing and exploring the biochemical biodiversity present in different natural environments. Here, we report the identification of a novel β-glucosidase from metagenomic DNA isolated from soil samples enriched with decaying plant matter from a Secondary Atlantic Forest region. For this, we employed a functional screening approach using an optimized and synthetic broad host-range vector for library production. The novel β-glucosidase - named Lfa2 - displays three GH3-family conserved domains and conserved catalytic amino acids D283 and E487. The purified enzyme was most active in pH 5.5 and at 50°C, and showed hydrolytic activity towards several pNP synthetic substrates containing β-glucose, β-galactose, β-xylose, β-fucose and α-arabinopyranose, as well as towards cellobiose. Lfa2 showed considerable glucose tolerance, exhibiting an IC50 of 300 mM glucose and 30% of remaining activity in 600 mM glucose. In addition, Lfa2 retained full or slightly enhanced activity in the presence of several metal ions. Further, β-glucosidase activity was increased by 1.7-fold in the presence of 10% (v/v) ethanol, a concentration that can be reached in conventional fermentation processes. Similarly, Lfa2 showed 1.7-fold enhanced activity at high concentrations of 5-hydroxymethyl furfural, one of the most important cellulase inhibitors in pretreated sugarcane bagasse hydrolysates. Moreover, the synergistic effect of Lfa2 on Bacillus subtilis GH5-CBM3 endoglucanase activity was demonstrated by the increased production of glucose (1.6-fold). Together, these results indicate that β-glucosidase Lfa2 is a promissory enzyme candidate for utilization in diverse industrial applications, such as cellulosic biomass degradation or flavor enhancement in winemaking and grape processing.